Identification of factors that influence the customer’s satisfaction of a recreational club by means of factorial analysis - Zanella, Andreia; de Lima, Leonardo Silva; Lopes, Luis Felipe Dias (Revista Gestão da Produção Operações e Sistemas, 2007)
This paper aims at identifying the relevant aspects regarding the use of services offered in a recreational club located in the central region of the state of Rio Grande do Sul, according to the customers’ perception. The knowledge of these aspects by the club becomes fundamental so that some efforts can be employed towards the dimensions highlighted as the most important ones, aiming at increasing the level of satisfaction and customers´ fidelization. For this purpose, a satisfaction survey questionnaire was elaborated, investigating issues related to services delivered by the club. For the data analysis, a factorial analysis statistics tool was used, which is one of the multivaried analysis tools, and it was possible to obtain a linear structure reduced from the original data set, by summarizing the information contained in a number of variables into a smaller set of factors. Six variables were highlighted: good service delivered by the employees; concern with customers’ interests; trustability in the services delivered; recognition of the customers’ needs; waiting time to be served and adequate structure. The knowledge of the important aspects in the customer’s satisfaction collaborates in the quality improvement in the process and for the continuity of consumption. Keywords: Customer satisfaction; Service quality; Recreational club; Factorial analysis.